2015
DOI: 10.1097/mpa.0000000000000292
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Polyenoylphosphatidylcholine in Rats With Severe Acute Pancreatitis

Abstract: Polyenoylphosphatidylcholine could reduce the damage to the pancreas through increasing pancreatic acinar cell membrane fluidity and pancreatic tissue calcium pump activity. Polyenoylphosphatidylcholine also scavenges oxygen free radicals and reduces lipid peroxide levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Nonetheless, Van Antwerpen et al [43] in their in vitro study showed that captopril, by inhibiting the MPO/HOCl system, was able to significantly reduce the oxidative modification of low-density lipoprotein in a dosedependent manner. Furthermore, Li et al [44] demonstrated that pathological injury of the lung in rats with intense acute pancreatitis was decreased with captopril treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, Van Antwerpen et al [43] in their in vitro study showed that captopril, by inhibiting the MPO/HOCl system, was able to significantly reduce the oxidative modification of low-density lipoprotein in a dosedependent manner. Furthermore, Li et al [44] demonstrated that pathological injury of the lung in rats with intense acute pancreatitis was decreased with captopril treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, early diagnosis is of great importance in patients with AP. Emerging studies provide evidence that pancreatitis leads to severe pathological changes in pancreatic acinar cells, and the damage of cells promotes the release of enzymes and organelles, which resulted in the occurrence of SAP [5]. Thus, strategies to promote pancreatic acinar cell apoptosis may have therapeutic potential in the treatment of AP.…”
Section: Introductionmentioning
confidence: 99%